Regional educational strategies - methods to promote human resource development in small businesses - Knapp, Kornelius [Verfasser]; Zschunke, Melanie [Verfasser] (My University, 2010)
"Over the next few decades, demographic change will cause significant changes in the working population. How businesses prepare for these changes will have a decisive impact on whether this transformation has a beneficial or detrimental effect on the economy. Small and mediumsized businesses do not possess the resources required to develop and implement sustainable human resource strategies and thus face particularly significant challenges. This article aims to outline the strategies that small and medium-sized businesses can implement to avert the dangers facing personnel management in the future. Expanding training advisory services and developing regional networks play a pivotal role here. While training advisory services can help to develop and implement the necessary measures, regional networks can support this implementation." (Autorenreferat, BIBB-Doku)
Keywords: G 1.1.1 Demografie; S 5.3 Personalentwicklung; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; S 2.4.2 Regionalentwicklung; Demografischer Wandel; Personalmanagement; Klein- und Mittelbetrieb; Unternehmen; Beschäftigungsfähigkeit; Regionales Netzwerk